Management of leaf spot of turmeric (Curcuma longa L.) incited by Colletotrichum capsici through fungicides - M Anandaraj, S Narasimha Rao, K Ravindra Kumar, (Journal of Spices and Aromatic Crops, 2012)
An experiment was conducted at Kammarpally (Andhra Pradesh) to evaluate the efficacy of four fungicides viz., Propiconazole (0.1%), Hexaconazole (0.1%), Tricyclazole (0.1%) and Carbendazim + Mancozeb (0.1%) for the management of leaf spot disease (Colletotrichum capsici) of turmeric (Curcuma longa L.). Rhizome treatment with Carbendazim + Mancozeb (0.1%) gave the best results for germination (90.52%) and rhizome treatment and foliar application of Propiconazole (0.1%) at 45 and 90 days after planting (DAP) were significantly superior in reducing the disease index (20.01%) of leaf spot disease and increasing the fresh rhizome yield (17.13 t ha-1) as compared to other fungicides tested. The high cost – benefit ratio was achieved in rhizome treatment and foliar application of Carbendazim + Mancozeb at 45 and 90 DAP (1:1.92).